Applying a stakeholder approach in FLR - Kusumanto, T. (ITTO, 2005)
This chapter looks at how forest landscape restoration (FLR) initiatives use a stakeholder approach to identify, understand and address the interests and concerns of key stakeholder groups. This kind of approach is important in FLR for two reasons. First, the success of FLR initiatives will depend on the willingness of stakeholder groups to cooperate with each other and with the FLR efforts. Second, since some stakeholders will be affected by the FLR activities, they need to be involved in decisions regarding the goods, services and processes of the landscape that are to be restored. Thus, a stakeholder approach will help achieve the goal of equitable benefit-sharing among the key stakeholder groups. Despite the importance of stakeholder approaches to FLR, caution is required when using them.